Worldwide long-term trends in the incidence of nonalcoholic fatty liver disease during 1990–2019: A joinpoint and age-period-cohort analysis - Wu, Wentao; Feng, Aozi; Ma, Wen; Li, Daning; Zheng, Shuai; Xu, Fengshuo; Han, Didi; Lyu, Jun (Frontiers in Cardiovascular Medicine, 2022)
Background: Nonalcoholic fatty liver disease (NAFLD) was previously a neglected disease that is now becoming a worldwide pandemic. A better understanding of its incidence and long-term trends will help to increase public awareness of the disease and the development of future prevention strategies. Methods: The incidence rates of NAFLD during 1990–2019 were collected from the Global Burden of Disease Study 2019 database according to the following parameters: sex, age, socio-demographic index, and geographical region. Estimated annual percentage changes and joinpoint models were used to assess the long-term trend of NAFLD, and an age-period-cohort model was used to assess the extents of the age, period, and cohort effects. Results: Adult males, postmenopausal females, Latin American populations, and people in developing countries had a high risk of developing NAFLD. The joinpoint model indicated a new trend of increasing NAFLD incidence in 2005. Age was a risk factor affecting NAFLD incidence, with this effect increasing in more-recent periods. Younger birth cohorts had lower risks of NAFLD. Conclusions: Recent prevention measures for NAFLD have achieved good initial results. However, it remains a high priority to increase the public awareness of this condition, develop its diagnostic criteria, identify cost-effective screening methods, and seek policy support to act against NAFLD, which will be a major public health problem in the future.